Measurement of the charge properties of articular cartilage by an electrokinetic method. - Minassian, A; O'Hare, D; Parker, K; Urban, J; Warensjo, K; Winlove, C (1998)
The charge structure of the surface of articular cartilage determines its interactions with the macromolecules and cells of synovial fluid. It may thereby be important to the physiological function and pathological degeneration of the tissue. To determine whether the electrokinetic properties of the surface differ from those of the bulk tissue, we measured the streaming potential generated by the flow of electrolyte over the surface of a cartilage plug mounted in a chamber built for that purpose. We then calculated the effective surface charge density. In nonfibrillated cartilage from the human femoral head, the surface charge density, 0.037+/-0.004 Cm(-2) (mean+/-SD), was approximately half that measured at the surface of slices cut from the middle and deep zones. In addition, the surface charge density fell relatively little at low pH; this is consistent with a higher proportion of strongly acidic groups. The variations in surface charge density were found to be similar to those in total fixed charge density in the slices by the tracer cation method. Therefore, no evidence exists that the actual surface differs in composition from the immediately underlying matrix. The addition of synovial fluid (0.0025 ml/ml) to the superfusing solution reduced the surface charge density by 25+/-9% (n=5), and we attributed this to the binding of synovial-fluid macromolecules.